Risk of Fracture with Thiazolidinediones: An Individual Patient Data Meta-Analysis - Bazelier, Marloes T.; de Vries, Frank; Vestergaard, Peter; Herings, Ron M.; Gallagher, Arlene M.; Leufkens, Hubert G.; van Staa, Tjeerd-Pieter (Frontiers in Endocrinology, 2013)
Background: The use of thiazolidinediones (TZDs) has been associated with increased fracture risks. Our aim was to estimate the risk of fracture with TZDs in three different healthcare registries, using exactly the same study design, and to perform an individual patient data meta-analysis of these three studies. Methods: Population-based cohort studies were performed utilizing the British General Practice Research Database (GPRD), the Dutch PHARMO Record Linkage System, and the Danish National Health Registers. In all three databases, the exposed cohort consisted of all patients (aged 18+) with at least one prescription of antidiabetic (AD) medication. Cox proportional hazards models were used to estimate hazard ratios (HRs) of fracture. The total period of follow-up for each patient was divided into periods of current exposure and past exposure, with patients moving between current and past use. Results: In all three registries, the risk of fracture was increased for women who were exposed to TZDs: HR 1.48 [1.37-1.60] in GPRD, HR 1.35 [1.15-1.58] in PHARMO and HR 1.22 [1.03-1.44] in Denmark. Combining the data in an individual patient data meta-analysis resulted, for women, in a 1.4-fold increased risk of any fracture for current TZD users versus other AD drug users (adj. HR 1.44 [1.35-1.53]). For men, there was no increased fracture risk (adj. HR 1.05 [0.96-1.14]). Risks were increased for fractures of the radius/ulna, humerus, tibia/fibula, ankle and foot, but not for hip/femur or vertebral fractures. Current TZD users with more than 25 TZD presciptions ever before had a 1.6-fold increased risk of fracture compared with other AD drug users (HR 1.59 [1.46-1.74]). Conclusion: In this study, we consistently found a 1.2- to 1.5-fold increased risk of fractures for women using TZDs, but not for men, across three different healthcare registries. TZD users had an increased risk for fractures of the extremities, and risks further increased for prolonged users of TZDs.